Spiritual Individu Menurut Psikospiritual Nabawi Untuk Pemulihan Golongan LGBT - Suriani Sudi; Noor Hafizah Mohd. Haridi; Khairul Hamimah Mohammad Jodi; Ahmad Munawar Ismail; Nasrudin Subhi; Siti Solehah Mat Aleh (USIM Press, 2024)
VOL. 27 (2022) Page(81-94)